Development of sex-linked PCR markers for gender identification in papaya - T.S, Chaithra; Singh, Kanhaiya; Prakash, Jai; Singh, S.K.; Hussain, Zakir; Gupta, N.C.; Kumar, R.R. (Indian Journal of Horticulture, 2024)
Papaya is an important fruit crop in the tropical and subtropical regions of the world, having several nutritional and numerous medicinal properties. It is a polygamous plant that has three primary sex forms, viz., male, female and hermaphrodite. Several methods are employed, based on morphological, physiological, and cytological factors, to detect the sex of plants at an early stage of growth. However, none of them proved effective, which led to the development of highly effective gene-based markers. In the present study, attempts were made to validate the molecular markers to determine the sex during the early stage of the plant. Out of the ten selected RAPD-SCAR markers, five SCAR markers showed amplification. Among the amplified markers, SDP, PKBT 5, and PMSM 2 proved most effective for identifying sex at the early developmental stage. These markers can be used commercially to select desired seedlings at an early stage for plantation